Protease-Activated Receptor-2 Regulates Neuro-Epidermal Communication in Atopic Dermatitis - Buhl, Timo; Ikoma, Akihiko; Kempkes, Cordula; Cevikbas, Ferda; Sulk, Mathias; Buddenkotte, Joerg; Akiyama, Tasuku; Crumrine, Debbie; Camerer, Eric; Carstens, Earl; Schön, Michael P.; Elias, Peter; et al. (Frontiers in Immunology, 2020)
Background Activation of protease-activated receptor-2 (PAR2) has been implicated in inflammation, pruritus, and skin barrier regulation, all characteristics of atopic dermatitis (AD), as well as Netherton syndrome which has similar characteristics. However, understanding the precise role of PAR2 on neuro-immune communication in AD has been hampered by the lack of appropriate animal models. Methods We used a recently established mouse model with epidermal overexpression of Par2 (Par2OE) and littermate WT mice to study the impact of increased Par2 expression in epidermal cells on spontaneous and house dust mite (HDM)-induced skin inflammation, itch, and barrier dysfunction in AD, in vivo and ex vivo. Results Par2OE newborns displayed no overt abnormalities, but spontaneously developed dry skin, severe pruritus, and eczema. Dermatological, neurophysiological, and immunological analyses revealed the hallmarks of AD-like skin disease. Skin barrier defects were observed before onset of skin lesions. Application of HDM onto Par2OE mice triggered pruritus and the skin phenotype. Par2OE mice displayed an increased density of nerve fibers, increased nerve growth factor and endothelin-1 expression levels, alloknesis, enhanced scratching (hyperknesis) and responses of DRG cells to non-histaminergic pruritogens. Conclusion Par2 in keratinocytes, activated by exogenous and endogenous proteases, is sufficient to drive barrier dysfunction, inflammation, and pruritus and sensitize skin to the effects of HDM in a mouse model that mimics human AD. Par2 signaling in keratinocytes appears to be sufficient to drive several levels of neuro-epidermal communication, another feature of human AD.